PEMANFAATAN SISTEM INFORMASI MANAJEMEN PUSKESMAS (SIMPUS) TERKAIT PELAYANAN PASIEN RAWAT JALAN DI PUSKESMAS GONDOKUSUMAN II YOGYAKARTA - , ASEP SETYA BUDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Based on interviews and direct observation, some of the menu at the Health Center SIMPUS Gondokusuman II Yogyakarta has not been thoroughly exploited. With this background, the authors are interested in discussing topics related to SIMPUS that used optimally and identify factors causing ketidakmaksimalnya SIMPUS use. In addition to these two authors will discuss the extent to which benefits are given by SIMPUS primarily related to outpatient care, ranging from patient to patient home sign. Goal: The objective of this study was to examine the use SIMPUS at the Health Center II Gondokusuman associated with outpatient services Method: This study uses descriptive qualitative approach and using a phenomenological design. Retrieval of data through interviews, observation, and study documentation. This is the subject of this reserach Gondokusuman II Yogyakarta health worker who uses SIMPUS MedCIS applications related to outpatient care. Object of this study is PHC Management Information Systems (SIMPUS) MedCIS Gondokusuman Health Center II in Yogyakarta. Result: The menu used SIMPUS associated with outpatient services at the health center of Yogyakarta is Gondokusuman II Registration Menu, Menu examination, and Menu Pharmacy. The menu is used and the registration menu while the menu Pharmaceutical Inspection Menu is not used at all. Factors causing disuse of the menu on SIMPUS related outpatient services based on the absence of the element of man to the officer training related to the use SIMPUS. Based on the lack of money element of a special budget SIMPUS maintenance. Based on the material elements, the old drug stock data can not be updated automatically with new drug stock data. Based on machine elements, software and computer SIMPUS frequent error loading time. Based element methods, the lack of Standard Operational Procedures and related instructions for use SIMPUS in doing service to the patient. Conclusion: Still the presence of a menu that has not been used by the health center staff Gondokusuman II Yogyakarta fullest.